Metode Tanya Jawab dalam Pembelajaran Al-Qur’an Hadis di SMAN 1 Panyabungan - Kholidah Nur; Laila Nur Sahwa; Muhammad Daswar; Wimra Sahara; Rizki Amanda; Panny Octaviani (PT. Willy Print Art, 2025)
This study aims to explain the use of the question and answer method in the Al-Qur'an Hadith learning process at SMAN 1 Panyabungan. This study adopts a qualitative approach, and data were obtained through direct interviews with teachers of these subjects. The results show that teachers begin learning activities by reading relevant verses to attract students' attention. The question and answer method is applied at the beginning, middle, and end of the learning session to gradually evaluate students' understanding. Teachers also provide media such as pictures, illustrations, and videos to increase student interest and design questions with a level of difficulty appropriate to their abilities. The students' response was quite positive, as seen from their increased participation and enthusiasm in answering and asking questions. One obstacle that arose was that some students felt less confident when participating. To overcome this problem, teachers provided encouragement, positive reinforcement, and additional rewards to boost students' courage. Overall, the question and answer method was considered effective in improving students' understanding and engagement in Al-Qur'an Hadith learning.